Implementation of PSAK 64 in Indonesian Oil and Gas Companies under Production Sharing Contracts - Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Tanjung, Amries Rusli; Jahrizal, Jahrizal; Dalil, M; Arief, Dodi Sofyan; Koto, Jaswar; Musa, Sulaiman; Veronica, Kristy (International Conference on Business Management and Accounting, 2025)
This study seeks to identify best practices, uncover implementation gaps, and provide recommendations to improve the quality and comparability of financial reporting in the sector. This study employs a qualitative case study approach to gain an in-depth understanding of the implementation of PSAK 64 in Indonesian oil and gas companies operating under the Production Sharing Contract (PSC) model. The sample is selected using purposive sampling, focusing on companies that: Operate in the upstream oil and gas sector in Indonesia, are governed by the PSC model, and have published financial reports in accordance with PSAK 64. The study findings reveal that while companies generally comply with the basic requirements of PSAK 64, there is considerable variation in the interpretation and application of specific provisions, particularly those related to the recognition, measurement, and disclosure of exploration and evaluation (E&E) assets. This study contributes to the accounting literature by highlighting how a single standard (PSAK 64) can be applied differently based on the contractual and regulatory environment.